1999
DOI: 10.1152/jn.1999.81.1.216
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Modulates Spike Backpropagation and Associated [Ca2+]iChanges in the Apical Dendrites of Hippocampal CA1 Pyramidal Neurons

Abstract: The effect of serotonin (5-HT) on somatic and dendritic properties was analyzed in pyramidal neurons from the CA1 region in slices from the rat hippocampus. Bath-applied 5-HT (10 microM) hyperpolarized the soma and apical dendrites and caused a conductance increase at both locations. In the dendrites (200-300 microm from the soma) trains of antidromically activated, backpropagating action potentials had lower peak potentials in 5-HT than in normal artificial cerebrospinal fluid. Spike amplitudes were about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Application of 1 M OH-DPAT reduced the dendritic Ca 2ϩ transients by 25.6 Ϯ 2.7% (n ϭ 5; 40 -100 m). This is consistent with the previously reported reduction of burst-induced Ca 2ϩ transients by 10 M 5-HT in CA1 pyramidal neurons (Sandler and Ross, 1999).…”
Section: Modulation Of Postsynaptic N-type Casupporting
confidence: 94%
See 2 more Smart Citations
“…Application of 1 M OH-DPAT reduced the dendritic Ca 2ϩ transients by 25.6 Ϯ 2.7% (n ϭ 5; 40 -100 m). This is consistent with the previously reported reduction of burst-induced Ca 2ϩ transients by 10 M 5-HT in CA1 pyramidal neurons (Sandler and Ross, 1999).…”
Section: Modulation Of Postsynaptic N-type Casupporting
confidence: 94%
“…For 10 M 5-HT a slight reduction of the amplitude of the backpropagating action potentials was reported (Sandler and Ross, 1999). To distinguish between these possibilities, we blocked Na ϩ and K ϩ channels (see Materials and Methods) and examined Ca 2ϩ channels in isolation in the whole-cell voltage-clamp configuration using 2 mM Ba 2ϩ as charge carrier (Fig.…”
Section: Modulation Of Postsynaptic N-type Camentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin acts through a different mechanism as it hyperpolarizes both the soma and apical dendrites (Sandler and Ross 1999). In this study, it was shown that serotonin has varying effects on back-propagating APs, depending on the neuronal compartment.…”
Section: Physiological Significancementioning
confidence: 81%
“…The properties of bis-fura 2 that distinguish it from fura 2 are the following: 1) the emitted fluorescence intensity is about twice that of fura 2, which allows reduction of dye concentration; 2) the K d is larger than that of fura 2, which expands the measurable [Ca 2ϩ ] range especially in the range above 500 nM of Ca 2ϩ ; and 3) it has more negative charges, which facilitate better dye retention within the cytosol. One of disadvantages of bis-fura 2 is that it has been provided commercially only as a cellimpermeable form that requires invasive loading methods (337).…”
Section: Bis-furamentioning
confidence: 99%